Economic analysis of aluminium conductor composite core and conventional aluminium conductor steel reinforced conductors in overhead ultra‐high voltage transmission lines. Issue 5 (20th December 2022) - Zhang, Yujiao; Sun, Hongda; Zhang, Xuankun; Chen, Zhiwei; Zhou, Li; Huang, Xiongfeng
Abstract: The application potential of aluminium conductor composite core (ACCC) conductors in the 1000‐kV power transmission line project deserves to be investigated. Its economic evaluation is a contentious issue. This paper proposes a method for selecting the type of conductors based on the life cycle cost (LCC) of a transmission line, which includes the initial investments, operation costs, maintenance costs, failure costs, and discard costs. The mathematical model of electromagnetic loss differs due to the various operational circumstances surrounding a transmission line; therefore, a novel three‐dimensional electromagnetic–fluid–thermal coupling model based on the finite element method (FEM) was proposed. The simulation error of ACCC and aluminium conductor steel reinforced (ACSR) conductors is 2.56% and 0.5%, respectively, compared to the experimental value. Subsequently, the LCC model is applied in the economic analysis of a 1000‐kV transmission line, and the costs of ACCC conductors and ACSR conductors under different annual power load utilization hours are calculated. The results indicate that the overhead power transmission line with ACCC conductors saves at least 2 × 10 6 ¥/km compared with ACSR when annual utilization hours reach 3500 h; meanwhile, energy saving benefits are achieved. Abstract : The topic of this paper is about using the LCC method to evaluate economic effectiveness of power transmission lines and drawing a conclusion that the power transmission lines of ACCC conductor can be more energy‐saving than ACSR's from a long‐term perspective.